Master's education for perfusion: is it needed? Is it important to future sub-specialization? - Syracuse PL; Beckley PD (Journal of Extra-Corporeal Technology, 1993)
This survey research measured the opinions of practicing perfusionists on the perceived need for a master's level perfusion degree, specialization within the field, attractors and barriers to education, and employer support for a master's degree. Descriptive and correlational analyses (including ANOVA) were performed upon 224 questionnaires received from the membership of The American Society of Extra-Corporeal Technology (AmSECT). A majority of the AmSECT population (58%) feels there is a need to recognize areas of specialization within perfusion. The top five choices for specialties are: pediatrics, support devices-pacemakers, perfusion education, phyisiology-hematology, and advanced perfusion study. The AmSECT practicing perfusionist membership's opinion on new entries into the perfusion field strongly favors baccalaureate level education (79%). This conclusion is supported by a majority of perfusionists regardless of their perfusion training. Of the respondents, 35% agreed there is a need for a master's degree, while 58% agreed there is a need to recognize areas of specialization within perfusion. This mixed support exists across demographic categories without respect to age, gender, years of practice, education, job title, number of cases a facility performs per year, or employment. Support for the degree arises from the belief it will: provide continuing education, benefit one's career, help establish specialty recognition, and provide personal and professional knowledge.